Ixazomib, Daratumumab, and Low-Dose Dexamethasone in Frail Patients With Newly Diagnosed Multiple Myeloma: The Hovon 143 Study. Issue 25 (1st September 2021) - Stege, Claudia A. M.; Nasserinejad, Kazem; van der Spek, Ellen; Bilgin, Yavuz M.; Kentos, Alain; Sohne, Maaike; van Kampen, Roel J. W.; Ludwig, Inge; Thielen, Noortje; Durdu-Rayman, Nazik; de Graauw, Nicole C. H. P.; van de Donk, Niels W. C. J.; et al.
Abstract : PURPOSE: Frail patients with newly diagnosed multiple myeloma have an inferior outcome, mainly because of a high discontinuation rate due to toxicity. We designed a phase II trial specifically for frail patients, evaluating the efficacy and tolerability of ixazomib-daratumumab-low-dose-dexamethasone (Ixa-Dara-dex). METHODS: Sixty-five patients, who were frail according to the International Myeloma Working Group frailty index, were treated with nine induction cycles Ixa-Dara-dex followed by maintenance with Ixa-Dara for a maximum of 2 years. RESULTS: The overall response rate on induction therapy was 78%. After a median follow-up of 22.9 months, median progression-free survival (PFS) was 13.8 months and 12-month overall survival (OS) was 78%. Median PFS and 12-month OS were 21.6 months and 92% in patients who were frail based on age > 80 years alone, versus 13.8 months and 78%, and 10.1 months and 70% in patients who were frail based on additional frailty parameters either ≤ 80 or > 80 years of age, respectively. In 51% of patients, induction therapy had to be discontinued prematurely, of which 6% because of noncompliance to study treatment, 9% because of toxicity, and 9% because of death (8% within 2 months, of which 80% because of toxicity). Quality of life improved during induction treatment, being clinically meaningful already after three induction cycles. CONCLUSION: Ixa-Dara-dex lead to a high response rate and improved quality of life. However, treatment discontinuation because of toxicity and early mortality, negatively influencing PFS and OS, remains a concern in frail patients. The outcome was heterogeneous across frail subpopulations. This should be taken into account in the design and interpretation of future studies in frail patients, to pave the way for more precise treatment guidance.